Penanaman Nilai-Nilai Pancasila bagi Siswa Pondok Pesantren Salafiyah Assyarif - Wardhono, Adhitya; Qori’ah, Ciplis Gema; Nasir, M Abd; Ubaidillah, Mohammad; Sifah, Isrina; Faizyah, Nadia Nurdiyana; Rachma P. A, Shabrina; Ferdyansyah, Dandy; Ma’arif, Samsul; Sarifudin, Ahmat; Puspito, Agung Nugroho; Prakoso, Bhim (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
This social project aims to reinforce the values of Pancasila to prevent their degradation. Additionally, the project seeks to enhance students' understanding of Pancasila values and alter their perspectives on the relevance of these values in daily life. The community service was conducted at the Salafiyah Assyarif Islamic Boarding School, Ajung District, Jember Regency, involving 20 students. The method employed is a conventional approach, incorporating presentations, practical activities, and discussions. The results indicate an 80% increase in the students' knowledge of Pancasila values